Advances in studies of nanoparticle–biomembrane interactions. (January 2015) - He, Xiao Cong; Lin, Min; Li, Fei; Sha, Bao Yong; Xu, Feng; Qu, Zhi Guo; Wang, Lin
Nanoparticles (NPs) are widely applied in nanomedicine and diagnostics based on the interactions between NPs and the basic barrier (biomembrane). Understanding the underlying mechanism of these interactions is important for enhancing their beneficial effects and avoiding potential nanotoxicity. Experimental, mathematical and numerical modeling techniques are involved in this field. This article reviews the state-of-the-art techniques in studies of NP–biomembrane interactions with a focus on each technology's advantages and disadvantages. The aim is to better understand the mechanism of NP–biomembrane interactions and provide significant guidance for various fields, such as nanomedicine and diagnosis.